FuoriUso '95 : caravanserraglio arte contemporanea - Cherubini, Laura; Marino, Antonella; Pietrantonio, Giacinto Di; Pioselli, Alessandra; Rubbini, Alice; Williams, Gilda (Pescara : Associazione Culturale Arte Nova, 1995)
Airo, Mario ; Alviani, Getulio ; Arienti, Stefano ; Armleder, John ; Art Club 2000 ; Beecroft, Vanessa ; Burkhart, Kathe ; Cattani, Giorgio ; Cattelan, Maurizio ; Chia, Sandro ; Cingolani, Marco ; Cucchi, Enzo ; Delvoye, Wim ; Fleury, Sylvie ; Garutti, Alberto ; Gonzalez-Foerster, Dominique ; Halley, Peter ; Hammons, David ; IRWIN ; Ispezione Medermeneutica ; Kopystianskaya, Svetlana ; Kopystiansky, Igor ; Kosuth, Joseph ; Kustera, Carter ; Leccia, Ange ; Lemieux, Annette ; De Leonibus, Enzo ; McCarty, Paul ; Montesano, Gian Marco ; Ontani, Luigi ; Opie, Julian ; Osmolovskij, Anatolij ; Paladino, Mimmo ; Pirri, Alfredo ; Pistoletto, Michelangelo ; Schifano, Mario ; Solakov, Nedko ; Spalletti, Ettore ; Steinbach, Haim ; West, Franz ; Wilson, Jane & Louise ; Woodrow, Bill ; Zvezdotchotov, Constantin
biog., bibliog. p. 144-166
Italiaans & Engels
FuoriUso '95 : Caravanserraglio arte contemporanea, 11 giugno - 11 luglio 1995
boek